Pemanfaatan Citra Quickbird dan Sistem Informasi Geografis untuk Kajian Tingkat Kerawanan Kecelakaan Lalu Lintas di Kota Yogyakarta - , ANNASTIVA KHALISA; , Dra. Endang Saraswati, M.S. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The study were to get variable data of interpretation Quickbird Image how showing the parameters also make the spatial modeling that affect of traffic accidents and give recommendations to decrease traffic accident. Collection of data sourced from Quickbird Image interpretation and secondary data . Quickbird Image gives data of landuse, turn radius, railway interesction, crossroad facilities, free view distance, traffic flow patterns, sidewalks, intersection control, and street mark. Secondary data gives the data of vehicle average speed and street attendence. Spatial modelling of traffic accidents use a weighted scorring methode. Validation was done by comparing with the frekuensi traffic accidents data. Quickbird Image gives compatible data parameters, it proofs with the landuse parameter can reach 90.01% accuracy. Spatial modelling result is a traffic accident risk map can be romendations given to decrease the traffic accident.